Hand hygiene in low- and middle-income countries. (September 2019) - Loftus, Michael J.; Guitart, Chloe; Tartari, Ermira; Stewardson, Andrew J.; Amer, Fatma; Bellissimo-Rodrigues, Fernando; Lee, Yew Fong; Mehtar, Shaheen; Sithole, Buyiswa L.; Pittet, Didier
Highlights: Hand hygiene is an effective strategy to reduce healthcare-associated infections. The 'My 5 Moments for Hand Hygiene' define when hand hygiene should occur. Low- and middle-income countries face unique challenges related to hand hygiene. Such challenges include overcrowding, or procurement of alcohol based handrub. Many low-resource settings have successfully implemented hand hygiene programs. Abstract: A panel of experts was convened by the International Society for Infectious Diseases (ISID) to overview evidence based strategies to reduce the transmission of pathogens via the hands of healthcare workers and the subsequent incidence of hospital acquired infections with a focus on implementing these strategies in low- and middle-income countries. Existing data suggests that hospital patients in low- and middle-income countries are exposed to rates of healthcare associated infections at least 2-fold higher than in high income countries. In addition to the universal challenges to the implementation of effective hand hygiene strategies, hospitals in low- and middle-income countries face a range of unique barriers, including overcrowding and securing a reliable and sustainable supply of alcohol-based handrub. The WHO Multimodal Hand Hygiene Improvement Strategy and its associated resources represent an evidence-based framework for developing a locally-adapted implementation plan for hand hygiene promotion.